PENATALAKSANAAN PENANGANAN JENAZAH PASIEN COVID-19 - Riefki Dwi Putra; Fahmi Fahmi; Yetti Yetti (Smart Education, 2022)
Abstract: Coronavirus Disease (Covid-19) is a very dangerous and deadly virus. The symptoms are almost the same as the flu in general, but this virus can cause severe infections and organ failure leading to death. Very many people have been infected by this virus, including in Riau as of January 20, 2021, as many as 27,714 people have been confirmed. The government has issued a Decree of the Minister of Health of the Republic of Indonesia Number HK.01.07/MENKES/413/2020 concerning Guidelines for the Prevention and Control of Coronavirus Disease 2019 (COVID-19). However, there have been many incidents of refusal to bury the bodies of Covid-19 patients according to the guidelines that have been determined by the government in various regions in Indonesia, including Riau. This research uses the Sociological Empirical method which later the author will provide an overview of the Management of the Body Handling of Coronavirus Disease 2019 (COVID-19) patients based on the Decree of the Minister of Health of the Republic of Indonesia Number HK.01.07/MENKES/413/2020 at the Pekanbaru City Government Hospital. Keywords: Corona Virus, corpse, government Abstrak: Coronavirus Disease (Covid-19) merupakan virus yang sangat berbahaya dan mematikan. Gejala yang dirasakan hampir sama dengan sakit flu pada umumnya, tetapi virus ini bisa mengakibatkan infeksi yang parah dan gagal organ berujung kepada kematian. Sangat banyak masyarakat yang terinfeksi oleh virus ini termasuk di Riau per 20 Januari 2021 sebanyak 27.714 orang terkonfirmasi. Pemerintah telah mengeluarkan Keputusan Menteri Kesehatan Republik Indonesia Nomor HK.01.07/MENKES/413/2020 Tentang Pedoman Pencegahan Dan Pengendalian Coronavirus Disease 2019 (COVID-19). Namun yang terjadi banyak peristiwa penolakan pemakaman jenazah pasien Covid-19 secara pedoman yang telah ditentukan pemerintah tersebut di berbagai daerah di Indonesia termasuk di Riau. Penelitan ini menggunakan metode Sosiologis Empiris yang nantinya penulis akan memberikan gambaran atas Penatalaksanaan Penanganan Jenazah Pasien Coronavirus Disease 2019 (COVID-19) berdasarkan Keputusan Menteri Kesehatan Republik Indonesia Nomor HK.01.07/MENKES/413/2020 di rumah Sakit Pemerintah Kota Pekanbaru. Kata kunci: Corona Virus, Jenazah, pemerintah